2018
DOI: 10.1038/s41467-018-03321-w
|View full text |Cite
|
Sign up to set email alerts
|

Divergent T-cell receptor recognition modes of a HLA-I restricted extended tumour-associated peptide

Abstract: Human leukocyte antigen (HLA)-I molecules generally bind short peptides (8–10 amino acids), although extended HLA-I restricted peptides (>10 amino acids) can be presented to T cells. However, the function of such extended HLA-I epitopes in tumour immunity, and how they would be recognised by T-cell receptors (TCR) remains unclear. Here we show that the structures of two distinct TCRs (TRAV4+TRAJ21+-TRBV28+TRBJ2-3+ and TRAV4+TRAJ8+-TRBV9+TRBJ2-1+), originating from a polyclonal T-cell repertoire, bind to HLA-B*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…More dramatic peptide movements have been reported for binding of the ELS4 TCR to HLA-B*35:01-EPLPQGQLTAY, with a large shift of 5Å occurring in the center of the peptide [5]. Also, a recent study demonstrated that two different TCRs, recognizing the same HLA-B*07:02 restricted NY-ESO-1 peptide, could stabilize the peptide in very different conformations [53]. Our study adds to the story of flexibility during T-cell antigen recognition, through a TCR induced shift in peptide primary anchor residue usage.…”
Section: Discussionmentioning
confidence: 85%
“…More dramatic peptide movements have been reported for binding of the ELS4 TCR to HLA-B*35:01-EPLPQGQLTAY, with a large shift of 5Å occurring in the center of the peptide [5]. Also, a recent study demonstrated that two different TCRs, recognizing the same HLA-B*07:02 restricted NY-ESO-1 peptide, could stabilize the peptide in very different conformations [53]. Our study adds to the story of flexibility during T-cell antigen recognition, through a TCR induced shift in peptide primary anchor residue usage.…”
Section: Discussionmentioning
confidence: 85%
“…The dynamic nature of peptides, especially those that are longer than 9 aa, in the HLA-binding groove is well established (57,58), as conformational plasticity plays an important role in enabling shape complementarity between TCR, peptide, and HLA. It is perhaps unsurprising that for highly dynamic peptides, multiple TCRs can recognize and bind the peptide in distinct conformations (19). However, 9-mer peptides, such as the NY-ESO-1 157-165 peptide, are usually more constrained, with different conformations typically being observed only as small backbone and side-chain rotamer movements (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that off-target peptides do not need to share sequence, physiochemical, or backbone geometry with the cognate peptide (61,62), and, in addition, multiple TCRs can bind distinct peptide hotspots on the same pHLA (17). In one instance, this was driven by conformational plasticity in the peptide (19). In this study, we build on these observations to demonstrate that TCRs that recognize distinct peptide hotspots in the same peptide can display nonoverlapping specificity profiles, thereby providing a mechanism by which TCRs could potentially evade thymic deletion caused by a specific self-peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also demonstrate that Tcell recognition was significantly alleviated when we broke the MHC I salt bridge with R66A and E163A mutations. Previously determined complex structure between HLA-B*07:02 and KFJ37 TCR showed that both the R62 and E163 of HLA-B*07:02 can form hydrogen bonds with the residues in the CDR3α and CDR1α loops of the TCR, respectively (Chan et al, 2018). This indicated that the residues in the salt bridge can be directly-recognized by the TCR (Tynan et al, 2007).…”
Section: Figurementioning
confidence: 97%